Bone impairment assessed by HR-pQCT in juvenile-onset systemic lupus erythematosus. Issue 5 (May 2016) - Paupitz, J.; Lima, G.; Alvarenga, J.; Oliveira, R.; Bonfa, E.; Pereira, R.
Abstract Summary High-resolution peripheral quantitative computed tomography (HR-pQCT) analysis of female juvenile-onset systemic lupus erythematosus (JoSLE) patients revealed trabecular/cortical bone damage and reduced bone strength primarily at the distal radius compared to healthy controls. We demonstrated for the first time that JoSLE patients with vertebral fracture (VF) present trabecular impairment at the distal radius. Introduction This study investigated the volumetric bone mineral density (vBMD), microarchitecture, and biomechanical features at the distal radius and tibia using HR-pQCT and laboratory bone markers in JoSLE patients compared to controls to determine whether this method discriminates JoSLE patients with or without VF. Methods We compared 56 female JoSLE patients to age- and Tanner-matched healthy controls. HR-pQCT was performed at the distal radius and tibia. Serum levels of the amino-terminal pro-peptide of type I collagen, the C-terminal telopeptide of type I collagen, intact parathormone, sclerostin, and 25-hydroxyvitamin D (25OHD) were evaluated. VFs were analyzed using VFA-dual-energy X-ray absorptiometry (DXA) (Genant's method). Results Reduced density and strength parameters and microarchitecture alterations of cortical and trabecular bones were observed in JoSLE patients compared to controls, primarily at the distal radius (p  < 0.05). Patients with VF exhibited a significant decrease in trabecular bone parameters solely at the distal radius (Total.BMD, p  = 0.034; Trabecular.BMD [Tb.BMD], p  = 0.034; bone volume (BV)/trabecular volume (TV), p  = 0.034; apparent modulus, p  = 0.039) and higher scores for disease damage (Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SLICC/ACR-DI), p  = 0.002). Bone metabolism markers were similar in all groups. Logistic regression analysis of parameters that were significant in univariate analysis revealed that Tb.BMD (OR 0.98, 95 % CI 0.95–0.99, p  = 0.039) and SLICC/ACR-DI (OR 7.37, 95 % CI 1.75–30.97, p  = 0.006) were independent risk factors for VF. Conclusion In conclusion, this study is the first demonstration of bone microstructure and strength deficits in JoSLE patients, particularly at the distal radius. Our results demonstrated that VF was associated with trabecular radius alteration and emphasized the potential detrimental effect of disease damage on this condition.